Contribution of Latex Micro Diagnosis to Modern Management of Rubber Plantations: Case of Clones With Low or Slow Metabolism PB 217 and PR 107 - Christophe, Adou Bini Yao; Mathurin, Okoma Koffi; Pacôme, Obouayeba Abba; Olivier, Atsin Guy Joël; Kouadio, Ballo Espérence; Jean-Lopez, Essehi; Jean, Wahounou Polié; Francis, Soumahin Eric; Hilaire, Kouakou Tanoh; Samuel, Obouayeba (European Scientific Journal, ESJ, 2018)
The cultivated rubber clones are sensitive to latex harvesting regimes according to their laticiferous metabolism. Thus, in order to determine the best latex harvesting systems of clones with low or slow metabolism, six latex harvesting technologies are applied to them in a bulk statistical device from Fisher to four rehearsals. The rubber is tapped in downward half spiral stimulated or not for nine years after the opening of the tapping panel. The agronomic parameters (production, vegetative growth), the tapping panel dryness and those of the latex micro diagnosis were evaluated. The results indicate that these clones independently of the latex harvesting system have good rubber productivity (2310 kg.ha -1 .y-1 ) with good radial vegetative growth (2.9 cm.y -1 ). Their trees show a well-balanced physiological profile and an acceptable sensitivity to the tapping panel dryness (4.9%). However, the physiological index, the bark consumption and the sensitivity to the tapping panel dryness lead to retain the latex harvesting technologies "S/2 d3 6d/7 Pa1(1) ET2.5% 4/y, S/2 d4 6d/7 Pa1(1) ET2.5% 4/y and S/2 d4 6d/7 Pa1(1) ET2.5% 8/yâ€ for the best. This index, favorably influencing the choice of technologies adapted to clones with active metabolism, contributes to the modern and efficient management of a rubber plantation.